2020
DOI: 10.1111/iej.13304
|View full text |Cite
|
Sign up to set email alerts
|

PRIRATE 2020 guidelines for reporting randomized trials in Endodontics: explanation and elaboration

Abstract: Well-designed and properly conducted randomized clinical trials provide a true estimate of the effects of interventions and are acknowledged as the gold standard in terms of clinical study design. However, the quality of randomized clinical trials published in the field of Endodontics is suboptimal. The Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 guidelines were developed exclusively for Endodontics by integrating and adapting the CONsolidated Standards of Reporting Trials (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…The trial was reported according to the Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 guidelines (Nagendrababu et al . 2020). The protocol was registered at the ClinicalTrials.gov Identifier: NCT03312153.…”
Section: Methodsmentioning
confidence: 99%
“…The trial was reported according to the Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 guidelines (Nagendrababu et al . 2020). The protocol was registered at the ClinicalTrials.gov Identifier: NCT03312153.…”
Section: Methodsmentioning
confidence: 99%
“…http://ClinicalTrials.gov databases (NCT/04700995). This manuscript has been written according to PRIRATE 2020 guidelines (Nagendrababu et al, 2020). A PRIRATE flowchart sets out the key stages of the study (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…All patients who participated in the study signed an informed consent form. The study report followed the CONSORT statements (Moher et al 2012) and the Preferred Reporting Items for Randomized Trials in Endodontics (PRIRATE) (Nagendrababu et al 2020).…”
Section: Methodsmentioning
confidence: 99%